Angiotensin II type 2 receptor–interacting protein 3a inhibits ovarian carcinoma metastasis via the extracellular HMGA2-mediated ERK/EMT pathway. Issue 6 (June 2017) - Huang, Ping; Guo, Liang; Xi, Jie; Wang, Donghui
Local migration and long-distance metastasis is the main reason for higher mortality of ovarian cancer. Microtubule-associated tumor suppressor 1/angiotensin II type 2 receptor–interacting protein is associated with tumor initiation and progression and exerts anti-tumor effects. High mobility group AT-hook 2 is overexpressed in majority of metastatic carcinomas, which contributes to carcinomas metastasis through Snail-induced epithelial-to-mesenchymal transition signal pathway. The purpose of this study was to investigate the signal pathway of microtubule-associated tumor suppressor 1/angiotensin II type 2 receptor–interacting protein–mediated anti-tumor effects. Our data observed that ovarian carcinoma cells exhibited lower expression of angiotensin II type 2 receptor–interacting protein 3a and higher expression of high mobility group AT-hook 2 compared to normal ovarian cells. Restoration of angiotensin II type 2 receptor–interacting protein 3a expression in ovarian carcinoma cells inhibited high mobility group AT-hook 2 expression and exhibited anti-proliferative effects. In addition, angiotensin II type 2 receptor–interacting protein 3a treatment suppressed the phosphorylation of epithelial-to-mesenchymal transition and extracellular signal–regulated kinase in ovarian carcinoma cells. We also observed that angiotensin II type 2 receptor–interacting protein 3a restoration downregulated expression of Snail, E-Cadherin, N-Cadherin, and Vimentin in ovarian carcinoma cells, whereas angiotensin II type 2 receptor–interacting protein 3a knockdown enhanced the phosphorylation of extracellular signal–regulated kinase and epithelial-to-mesenchymal transition. In vivo assay indicated that angiotensin II type 2 receptor–interacting protein 3a inhibited ovarian tumor growth and elevated survival of tumor-bearing immunodeficient mice. Tumor histological analysis indicated that Snail, E-Cadherin, N-Cadherin, and Vimentin expression levels were downregulated via decreasing high mobility group AT-hook 2 expression. Furthermore, upregulation of angiotensin II type 2 receptor–interacting protein 3a impaired the phenotype of extracellular signal–regulated kinase and epithelial-to-mesenchymal transition in ovarian carcinoma cells and tumor tissues. Taken together, angiotensin II type 2 receptor–interacting protein 3a presents potential in suppressing the proliferation and aggressiveness of ovarian carcinoma cells through the high mobility group AT-hook 2–mediated extracellular signal–regulated kinase/epithelial-to-mesenchymal transition signal pathway.